Virus-Host Interactions in HIV Pathogenesis: Directions for Therapy - Levy, J.A. (SAGE Publications, 2011)
The challenge of controlling HIV infection involves an understanding of the heterogeneity of the virus, its wide cellular host range, its primary routes of transmission, and the immunologic and intrinsic cellular factors that can prevent its transmission and replication. Identification of HIV-infected individuals who have survived more than 10 years without signs of the infection and without therapy encourages studies examining the natural mechanisms for resistance to infection and disease. Within the immune system, emphasis should be given to the innate or natural response that appears within minutes of the infection and offers the optimal time for controlling HIV. All these parameters in HIV pathogenesis underline the information needed to develop optimal anti-HIV therapies and an effective AIDS vaccine.